THE USE OF INDEX CARD MATCH COLLABORATED WITH GROUP DISCUSSION TO IMPROVE STUDENTS READING COMPREHENSION OF RECOUNT TEXT - Mustofa, Habib; Susilawati, Endang; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: PenelitianiniberjudulPenggunaanPencocokanKartu Index dikolaborasikandenganDiskusiKelompokuntukmeningkatkanKemampuanpemahamanmembacasiswaterhadapteksberbentuk recount. Tujuandaripenelitianiniadalahuntukmembantumengatasikesulitansiswadalammemahamiteksberbentukrecount.SubjekpenelitianadalahsiswakelasVIIIF; yang berjumlah 31siswa.Penelitianinidilaksanakansebanyaktigasiklus.Penelitimenggunakantesjawabansingkat, tabelpengamatan, dancatatanlapangansebagaialatpengumpul data.Hasilpenelitianmenunjukanpeningkatanpemahamansiswadidalammembacadarisikluspertamasampaipadasiklusakhir.Initerlihatdarijumlahsiswa yang mencapai Standard ketuntasan minimum di siklusterakhir(87,10% atau 27 siswa). Sesuaidengan target daripenelitianiniuntukmembuat 80 % siswamencapai KKM (70). Sementara rata-rata nilaipencapaiansiswameningkatdari62.42ke81.45.Sebagaihasilnya, penulismenyimpulkanbahwaPencocokanKartu Index dikolaborasikandenganDiskusiKelompokmampumeningkatkanpemahamanmembacasiswaterhadapteks recount dengansangatbaik. Kata Kunci: PencocokanKartu Index, PemahamanMembaca Abstract:This research entitled the use of index card match collaborated with group discussion to improve students reading comprehension of recount text. The purpose of this research is to solve the students problem which was their difficulty in comprehending the recount text. The subject of this research was class VIIIF; which consisted of 31 students. This research was done in three cycles. The researcher used short answer tests, observation checklist tables, and field notes as the tools of collecting data. The research finding showed that the students reading comprehension improved from the first cycle to the last cycle. It is showed by the number of the students who passed the Standard of minimum score in the last cycle (87,10 % or 27 students). As the target of this research is to make 80 % of students passed the KKM (70). While, it is supported by the mean score of students achievement improved from 62.42 to 81.45. As the result, the writer concludes that Index Card Match collaborated with Group Discussion improved students reading comprehension of recount text very well. Keywords: Index Card Match, Reading Comprehension